Safety and efficacy of l‐arginine produced by fermentation using Corynebacterium glutamicum KCCM 10741P for all animal species. (25th May 2018) - ; Rychen, Guido; Aquilina, Gabriele; Azimonti, Giovanna; Bampidis, Vasileios; Bastos, Maria de Lourdes; Bories, Georges; Chesson, Andrew; Cocconcelli, Pier Sandro; Flachowsky, Gerhard; Gropp, Jürgen; Kolar, Boris; et al.
Abstract: l ‐Arginine is considered to be a non‐essential amino acid for most adult mammalian species, but it is classified as essential for birds, fish, possibly reptiles and also for strict carnivores. The product subject of this assessment is l ‐arginine produced by fermentation using a non‐genetically modified strain of Corynebacterium glutamicum (KCCM 10741P). It is intended to be used in feed and water for drinking for all animal species and categories. Species identity of the production organism was confirmed and the strain was sensitive to antibiotics at concentrations at or below thresholds specified by EFSA; thus, C. glutamicum KCCM 10741P may be considered safe by the qualified presumption of safety (QPS) approach. No viable cells of C. glutamicum were detected in the final product. The amount of identified material exceeded 99.8%, and no impurities of concern were detected. The use of l ‐arginine produced by C. glutamicum KCCM 10741P is safe for target species when supplemented to diets in appropriate amounts, for the consumer and the environment. l ‐Arginine produced by C. glutamicum KCCM 10741P is considered corrosive to skin and eyes and therefore poses a risk by inhalation. The additive is an effective source of arginine for all species. For the supplemental l ‐arginine to be as efficacious in ruminants as in non‐ruminant species, it requires protection against microbial degradation in the rumen.